Pelatihan Roti Home Industri Berbasis Gereja untuk Pemberdayaan Ekonomi Perempuan di GPIA Sidoasri Malang - Rubby Julius Tjin; Erlin Dewi Sartika; Ester Yunita Dewi (Institut Nalanda, 2026)
This community service activity was carried out by students of STT Kadesi Bogor at GPIA Sidoasri, Malang, East Java, on January 21–22, 2026. The program aims to empower church women through home industry-based bread-making training as a concrete effort to improve family economic conditions. A total of 15 participants attended the two-day training, which included introductions to raw materials, dough composition, processing techniques, dough shaping, filling variations, and baking processes. On the second day, all participants successfully practiced independently in producing soft and high-quality bread. This training also provided an understanding of production cost calculation and profit potential, where with an initial capital of IDR 86,500, participants were able to produce 30 pieces of bread with an estimated profit margin of around 65%. After the training, participants began applying their skills by marketing the bread during Sunday church services, with average sales reaching 100 pieces per week. The results show that church-based skills training integrated with biblical values is effective in equipping church women with entrepreneurial abilities. In addition, the program contributes to improving sustainable family economic independence without changing the original meaning of the activity.